Exploring Lecturers’ Perceptions of Multiple Intelligence-based Instruction in Teaching English for Islamic Studies - Sahril, Sahril; Basri, Muhammad; Nur, Sahril (Tamaddun Life, 2024)
This paper aims to explore lecturers’ perceptions on multiple intelligence-based instruction in teaching English for Islamic studies. The key question is how lecturers understand the concept of MI-based instruction. This study was conducted at one of the Islamic universities in Indonesia involving three lecturers. The instruments used were multiple intelligence inventory questionnaires and interview guidelines. The data found that teaching and learning activities should be designed to enhance each student's different intelligences, facilitating strength intelligence. Students not only have language and mathematics intelligence but also have several different intelligences owned by students, including: verbal linguistic, logical-mathematical, musical, visual-spatial, bodily kinesthetic, naturalistic, intrapersonal, interpersonal, and existential intelligence. MI-based teaching provides a new outlook in improving the quality of teaching and meaningful learning. MI-based instruction respects each student's learning style, which is indicated by the student's preference in learning. Therefore, using MI-based instruction in the teaching and learning process will be easy, fun, and respect everyone's way of receiving material. This study encourages future research on connecting the understanding of the multiple intelligences of lecturers with the needs of students in the process of learning English for Islamic studies.